Feiyanning formula modulates the molecular mechanism of osimertinib resistance in lung cancer by regulating the Wnt/β-catenin pathway - Sang, Shuliu; Sun, Chenbing; Ding, Rongzhen; Jiang, Jingjie; Han, Yang; Gan, Shanshan; Bi, Ling; Gong, Yabin (Frontiers in Pharmacology, 2022)
Feiyanning Formula, a Chinese herbal formula ,is derived from summarized clinical experience and has anti-lung cancer effects. Osimertinib, a third-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), can improve PFS and survival of patients, while drug resistance cannot be avoided. In vitro and in vivo experiments were used in this study to investigate the mechanism of Feiyanning Formula in delaying drug resistance in lung cancer. The cell proliferation ability was detected by the osimertinib-resistant cell counting kit-8 (CCK-8) and colony formation. The effect of the Feiyanning Formula on cellular migration and invasion of lung cancer osimertinib-resistant cells was evaluated by wound healing and transwell assays. Body weight and tumor volume of mice were measured weekly after subcutaneous inoculation of HCC827OR cells in various gavage groups. The potential molecular mechanisms were explored by RNA and Western blot experiments. The results showed that Feiyanning Formula combined with osimertinib significantly inhibited the proliferation, migration, and invasive activities of non-small cell lung cancer (NSCLC) resistant cell lines PC9OR and HCC827OR. Furthermore, subcutaneous transplantation tumor animal experiments demonstrated that Feiyanning Formula is anti-tumor growth. Furthermore, we found that when Feiyanning Formula was applied to NSCLC-resistant cells, the mRNA expression of SRSF1 and GSK3B was downregulated, as was the protein expression of SRSF1, β-catenin, and GSK3B, which was related to the Wnt/β-catenin pathway. This research suggested that Feiyanning Formula causes osimertinib resistance by regulating the Wnt/β-catenin pathway.